Sustainable Development Education in Times of the Post Era: Challenges, Opportunities, and Strategies for Digital Transformation in Language Learning and Teaching - Larsari, Vahid Norouzi (International Journal of Social Learning (IJSL), 2024)
The COVID-19 pandemic abruptly shifted language education to online platforms, presenting challenges and opportunities for digital transformation. Over 1.5 years, digital education became essential, forcing millions of language educators and institutions to adapt to remote instruction. This article aims to understand and make known the consequences of the Post-COVID-19 pandemic specifically in digital transformation in language learning and teaching. This article examines the impact of the post-COVID-19 era on the digital transformation of language learning and teaching. The researcher systematically searched academic literature published between 2020 and 2022, using databases like Google Scholar, PubMed, and ScienceDirect, focusing on keywords related to COVID-19, language learning, teaching, and online education. By analyzing various documentary sources, the study explores how educators and learners have navigated online platforms, identifying difficulties and innovative strategies that emerged during the transition.